BAHASA INGGRIS - Nida Farhana; Novanita Whindi Arini (Postgraduate, University of Mataram, 2023)
: Â The water cycle is science material for grade 5 in elementary schools, this lesson is very important because it relates to student experiences or real life. Not a few students have difficulty in learning it. Therefore researchers created Chatbot Rain to develop and produce products that help students better understand concepts and can improve learning outcomes in the process of learning water cycle material. This study uses research and development (R&D) methods with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The analysis technique used is qualitative and quantitative which are then converted into a Likert Scale Interpretation table with a range of 5 scales. The research was conducted in several elementary schools with media applications that had been validated by media experts, material experts, and education experts as well as feasibility trials with small and large trials. The validation results of media experts were 88.23%, material experts were 92%, and education experts were 90% while media feasibility tests with large and small trials produced scores of 86.8% and 89.2%. While the effectiveness test obtained a score of 80.71%. Based on the results of these percentages, it can be concluded that the Chatbot Rain media is very feasible and effective to use and develop in the water cycle learning process in elementary schools.